The Use of Audiovisual Learning Media to Enhance Digital Literacy Competence in Indonesian Language Learning Among Fifth-Grade Students at SDN 02 Baleharjo - Prayitno, Harun Joko; Fitriany, Devinda Nur; Purnomo, Eko; Andyani, Rhavida Anniza; Adhantoro, Muhammad Syahriandi; Kurniaji, Ganno Tribuana; Jufriansah, Adi (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2024)
Information technology has become essential in human life. Coping with this era requires a new literacy that leverages digital tools to enhance literacy skills. By acquiring digital literacy, it is hoped that students can become more critical and creative in selecting information. In education, digital literacy plays a vital role in developing learning materials that foster students curiosity and creativity. Learning media is indispensable for teachers in facilitating the learning process. Learning media plays a crucial role in helping teachers explain learning concepts effectively in the classroom. Learning the Indonesian language in elementary schools plays a significant role in developing language skills such as reading, writing, and listening. In this research, the researchers employed the classroom action research (CAR) method, aimed at addressing problem-solving or making improvements at SDN 02 Baleharjo, Pacitan. The study involved 20 fifth-grade students, comprising 10 male students and 10 female students. The research results indicate that the effectiveness of audiovisual learning media in improving digital literacy competence in Indonesian language learning can increase, resulting in better outcomes compared to learning without the use of audiovisual media.